Self-Love among Javanese Women: A Phenomenological Study in Cultural Context - Sonderi, Akbar (LifeSciFi, 2025)
Self-love is often understood as an individual psychological process, yet in collectivist cultures it is profoundly shaped by social and cultural expectations. This study explores how Javanese women experience and express self-love within the framework of traditional Javanese values. Using a qualitative phenomenological approach, in-depth interviews were conducted with three Javanese women aged 23–29 years living in the Special Region of Yogyakarta. The findings reveal that self-love manifests primarily through filial devotion to parents, freedom of choice exercised within cultural boundaries, and conscious self-care and personal development. Key supporting factors include family encouragement, positive social relationships, an attitude of sincere acceptance, and healthy self-esteem. However, patriarchal norms, age hierarchy, and fear of social judgment remain significant barriers to fuller expression of self-love. The study concludes that self-love among Javanese women is essentially relational and context-bound, requiring a delicate balance between personal well-being and cultural obligations. These insights highlight the importance of understanding self-love as a culturally embedded phenomenon rather than a universal individual trait.